ACCOUNTS RECEIVABLE AND INVENTORY ACCOUNTING IN SUPPORTING REGIONAL FINANCIAL TRANSPRANCY (CASE STUDY OF NORTH ACEH DISTRICT GOVERNMENT IN 2021) - Muammar Kaddhafi; Sri Dewi Wahyuni; Aura Humayrah; Ulfa Zuhra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Receivables and inventory are two important elements in financial statements that affect the financial health of a company. Effective management and accurate recording are essential to improve transparency and reliability of financial statements. This article aims to analyze the recognition, presentation, and evaluation of the efficiency of receivables and inventory based on the financial statements of the North Aceh Regency Government in 2021. The research method used is a literature review with a qualitative descriptive approach with a document study approach. The results of the study indicate that the management of receivables, especially tax receivables and other PAD, still requires improvement in terms of collection and control. Meanwhile, inventory management shows good efficiency with optimal turnover. The application of receivables and inventory accounting in accordance with Government Accounting Standards (SAP) can improve the quality of transparency and accountability of regional finances.